Perbandingan Sistem Pemidanaan antara Hukum Islam dan Hukum Positif Indonesia dalam Penanganan Tindak Pidana Pencurian - Samsul Bahri; Anggara Sasmita; Haryadi Hamzah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to analyze the comparative sentencing systems between Islamic law and Indonesian positive law in addressing theft crimes. In Islamic law, theft (sariqah) is considered a serious violation of individual property rights and social order, punishable by hand amputation if certain conditions are met. Meanwhile, under Indonesian positive law, theft is regulated in the Criminal Code (KUHP) and punishable by imprisonment, taking into account elements such as intent, culpability, and the circumstances of the offender. This research employs a normative juridical approach with a comparative method to examine the philosophical foundations, principles of justice, and purposes of punishment within both legal frameworks. The findings reveal that Islamic law emphasizes prevention and deterrence through firm but just punishment grounded in faith and moral responsibility. In contrast, Indonesian positive law focuses on rehabilitation and the protection of human rights, guided by humanitarian principles and social justice. Although both systems differ in their implementation and philosophical underpinnings, they share a common objective: to maintain social order, protect property rights, and uphold justice. These insights are expected to contribute to the development of a national legal system that harmonizes moral, ethical, and humanitarian values.